Polyvascular disease: A narrative review of current evidence and a consideration of the role of antithrombotic therapy. (December 2020) - Weissler, E. Hope; Jones, W. Schuyler; Desormais, Ileana; Debus, Sebastian; Mazzolai, Lucia; Espinola-Klein, Christine; Nikol, Sigrid; Nehler, Mark; Sillesen, Henrik; Aboyans, Victor; Patel, Manesh R.
Abstract: Background and aims: Polyvascular disease (PVD) affects approximately 20% of patients with atherosclerosis and is a strong independent risk factor for ischemic outcomes. However, guidelines do not address screening or treatment for PVD, and there have been no PVD-specific trials. We reviewed subgroup analyses of large randomized controlled trials of more intense antithrombotic therapy to determine whether increased intensity of therapy improved ischemic outcomes in patients with PVD. Methods: MEDLINE, MEDLINE in-Process, EMBASE, and the Cochrane Library were queried for randomized controlled trials larger than 5000 patients evaluating secondary prevention therapies in patients with coronary artery disease or lower extremity peripheral artery disease. Results: Thirteen trials were included ranging in size from 7243 to 27, 395 patients. In 9 trials (CHARISMA, TRA 2°P–TIMI 50, PEGASUS—TIMI 54, VOYAGER PAD, TRACER, EUCLID, TRILOGY ACS, PLATO, and COMPASS), patients in the PVD subgroup treated with increased-intensity antithrombotic therapy had similar or greater relative risk reductions for ischemic events in comparison with the general trial cohorts. In four trials (DAPT, THEMIS, APPRAISE-2, and ATLAS ACS 2 TIMI 51), the PVD subgroup had an increased hazard of ischemic events with increased-intensity therapy compared with the general trial cohorts. Conclusions: More intense antithrombotic therapy in patients with PVD was associated with a similar relative risk reduction for ischemic events compared with patients without PVD. Therefore, patients with PVD benefit from a larger absolute risk reduction because of their higher baseline risk. Future trials in patients with atherosclerotic cardiovascular disease should intentionally include PVD patients to adequately assess treatment options for this under-studied, under-treated population. Graphical abstract: Image 1 Highlights: Polyvascular disease (PVD) is a strong independent risk factor for ischemic outcomes. We reviewed 13 antithrombotic RCTs ranging in size from 7243 to 27, 395 patients. We assessed if increased intensity therapy improved ischemic outcomes in PVD. PVD patients had similar or greater ischemic risk reduction with more intense therapy. Intensive therapy in PVD does not seem to be associated with increased bleeding risk.